2003
DOI: 10.1007/s00268-003-7234-y
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Classification of Chronic Pancreatitis

Abstract: Chronic pancreatitis has been defined by features that are clinical and etiologic in origin. From such definitions a number of classifications have been developed, starting with the Marseille Classification in 1963. Defining features of chronic pancreatitis must consider the etiology of the disease, which then presents characteristic clinical evidence through symptomatic sequelae of organ pathology, including complications of the disease. Advancing technology has improved the imaging capabilities available to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Although there has been recent recognition of the wider impact of CP on patients' psychological and social well-being, and the burden of living with the condition has been recognised, it is not well documented. 4,6,7 In the majority of QoL studies, the focus was on measuring QoL before and after an intervention and not on comparing QoL in those with chronic pancreatitis and a healthy control group. This suggests that the primary goals for patients with CP are intervention-based, thus perpetuating the notion that interventions are a panacea for QoL issues.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been recent recognition of the wider impact of CP on patients' psychological and social well-being, and the burden of living with the condition has been recognised, it is not well documented. 4,6,7 In the majority of QoL studies, the focus was on measuring QoL before and after an intervention and not on comparing QoL in those with chronic pancreatitis and a healthy control group. This suggests that the primary goals for patients with CP are intervention-based, thus perpetuating the notion that interventions are a panacea for QoL issues.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pancreatitis is characterized morphologically by a progressive pancreatic fibrotic process [1] . Extracellular matrix (ECM) components are distributed in both healthy and diseased pancreas, and there is an increased deposition of disorganized ECM components in chronic pancreatitis [2] .…”
Section: Introductionmentioning
confidence: 99%
“…7- 9 The degree of pancreatic fibrosis could thus be a useful indicator for evaluating the pa thological conditions of the p ancreas, even the pancreatic remnant following a pancreaticoduodenectomy. The authors previously demonstrated a time-signal in tensity curve (TIC) of the pancreas obtained from dynamic contrast-enhanced magnetic resonance imaging (MRI) to be a reliable and non-invasive monitoring technique for a precise evaluation of the histological degree of pancreatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%